Teacher Training on the "Aktif Bergerak" Interactive Pocket Book for Health Literacy Promotion - Junaidi Budi Prihanto; Taufiq Hidayat; Irma Febriyanti; Arifah Kaharina; Aby Nugrah Septanto; Novadri Ayubi (GANDRUNG: Jurnal Pengabdian Kepada Masyarakat, 2026)
Insufficient physical activity and increasing sedentary behavior among adolescents remain major public health concerns, highlighting the need to strengthen health literacy through school-based interventions. Physical Education, Sports, and Health (PJOK) teachers play a strategic role in promoting active lifestyles, yet they require innovative learning resources to support effective health education. This community service program aimed to improve the health literacy of junior high school PJOK teachers through training on the use of the Aktif Bergerak Interactive Pocket Book. The program involved 13 PJOK teachers from the Nganjuk Regency Subject Teacher Association (MGMP). Activities included needs assessment, workshop-based training, interactive demonstrations, and hands-on practice using the pocket book. Program effectiveness was evaluated using pretest–posttest health literacy assessments, participant evaluations of the learning media, and satisfaction questionnaires. The findings showed a significant improvement in teachers' health literacy scores, with the mean score increasing from 61.54 to 76.15 (p = 0.007). Participants also rated the interactive pocket book highly in terms of content quality, attractiveness, usability, and visual design, while expressing high satisfaction with the implementation of the training. These findings indicate that the Aktif Bergerak Interactive Pocket Book is a practical and effective educational resource for enhancing teachers' health literacy and supporting the promotion of physically active lifestyles in junior high schools.